The position of music in culture - Helder, Lorena Margeurite (My University, 1894)
Introduction: Individuality is the basis of culture. Our student must have a power by his culture which uses books, arts, facilities, and elegances of speech, but is not subdued by them, or lost in them. Only he who has a good determination is a well-made man and the end of culture is not to destroy this determination, but to take away all other things and leave power alone in its purity. Our student must have a style and determination that will enable him to master his own specialty. He must possess the power to see every object with a free and disengaged look so that while he is speaking of the object before him he is not thinking of himself and trying to catch your admiration. Culture is the suggestion of the best thoughts. A cultured man has a range of affinities through which he can modulate the violence of certain master tones that have too great a prominence in his scale. It makes up his balance; puts him among his equals and superiors; awakens that delightful sense of sympathy; and warns him of the dangers of solitude and repulsion. ‘Tis not a compliment, but rather otherwise, to consult a man on the races, books, art, or music, whenever he appears; or to turn the conversation to the subject he is known to fondle, when he approaches. He must leave our pets at home when we go into the street and meet men on broad grounds of good sense and meaning.
Citation: Helder, Lorena Margeurite. The position of music in culture. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Music; Culture; Civilization; Public; Class; Anthropology; Theses; Manuscripts (documents)